Розробка технології купажованих тваринно-рослинних жирів підвищеної харчової цінності - Радзієвська, Ірина Гіронтіївна (My University, 2010)
Дисертація на здобуття наукового ступеня кандидата технічних наук за спеціальністю 05.18.06 – технологія жирів, ефірних масел і парфумерно-косметичних продуктів. – Національний університет харчових технологій, Київ, 2009. Дисертацію присвячено розробленню науково обґрунтованої технології функціональних жирових продуктів – комбінованих сумішей на основі тваринних жирів та рослинних олій, яка дає змогу підвищити харчову і фізіологічну цінність та забезпечити стабільність технологічних властивостей продукту в процесі виробництва та зберігання. Отримано математичні описи залежностей терміну зберігання купажованого жиру від температури зберігання продукту, сумарного вмісту ізомерів токоферолу та вмісту β-каротину у ньому. Показано, що за сумарною щільністю вмісту біологічно активних речовин купажовані жири переважають над природними жирами. Встановлені оптимальні параметри процесу купажування. Розроблено програму для швидкого визначення кількісного складу купажів зі збалансованим жирнокислотним складом. Розроблено експрес-методику аналізу для визначення малих кількостей тваринних жирів у комбінованих жирових продуктах. Встановлено доцільність використання купажованого жиру у виробництві жирових та м'ясних продуктів. Оптимальні рецептури та технологію апробовано у промислових умовах. Розраховано економічну ефективність впровадження наукової розробки у виробництво. Розроблено проект нормативної документації на новий вид продукту – купажований жир. Пріоритетність досліджень підтверджено 2 Патентами України на корисну модель. Thesis for the Degree of Doctor of Philosophy (PhD) in technology, Speciality 05.18.06 – technology of fats, essential oils and perfume-cosmetic products. – National university of food technologies, Kyiv – 2009. The work was aimed on the development of the scientifically grounded technology of the special fats product – combined mixtures on the basis of adipose and vegetable oils, which enables to promote a food value and provide stability of technological properties of product in the process of production and storage. By the basic index of biological and accordingly food value of fats there is content of fat acids. Natural fats do not answer requirements, which are pulled out to biologically valuable fat, to balanced after fatty acid composition. After the conclusions of dietitians fatty acid composition of separate fats does not answer optimum correlation of saturated, monosaturated and polysaturated of fat acids. It is important, that correlation of PS of families omega 6 and omega 3 made not more than 10:1, but in the cases of violation of lipidic exchange – 5:1 and even 3:1. The analysis of results of actual feed of population testifies that really these PS act to the organism of human in correlation from 10:1 to 30:1. The possible variant of decision of problem of improvement of physiology properties of adiposes is blend of them with vegetable oils. As vegetable oils are the source of natural antioxidants pre-conditions are created for development of technology of blending animal-vegetable fat the optimized fatty acid composition with the prolonged term of storage. Work is probed by possibility of braking of processes of hydrolytic and oxidative spoilage of adiposes at adding to them of vegetable oils in different amounts. Substantial deceleration of processes of peroxidation is found out in pre-production models with the refined corn and unrefined by mustard and soy-bean oils by comparison to control. Best results are given by additions to pork fat: introduction 20% corn oil prolongs the term of storage in 2,3 times 30% mustard oil – in 2 times, 10% soy-bean oil – in 1,6 times. It is shown, that braking of processes of oxidative spoilage of adiposes at addition to them of vegetable oils is related to the increase of concentration of natural antioxidants in a mixture. Mathematical descriptions of dependence term of saving of blending fat are collected from the temperature of saving of product, total maintenance of isomers of tocopherols and maintenance of β-carotin in him. The guarantee term of storage of blending fats is set in the range of temperatures from 60 to minus 8°C. Optimum composition of blend is set, that allows not only to promote firmness of product to oxidation but also balance fatty acid composition. It is shown, that after the total closeness of maintenance biologically active matters blending fats prevail above natural fats, in addition, they less atherogenic and more protected from peroxidative oxidation. Set optimum parameters of process of blending. The technological chart of receipt of blending fat is developed; the complete set of equipment of firm is neat by “Tetra-Otich” productivity 1000 kg/h. The program is developed for rapid determination of quantitative composition of blend with the balanced fatty acid composition. The express instrumental method of analysis is developed for determination of a few of adiposes in the combined fatty products. Expedience of the use of blending fat is set in production of fatty and meat products. The optimum compounding and technology is approved in industrial terms. Eexperimental-industrial party of margarines on the basis of blending fat is produced on Joint-stock COMPANY of “Zaporozhian оliyagircombinat”. Eexperimental-industrial party of the boiled constitutional sausages on the basis of meat of bird is made on Joint-stock COMPANY “Kiev meatprosess factory”. Economic efficiency of introduction of scientific development is led to in production. The project of normative document on a new type of product is developed - blending fat. The results of researches are confirmed by Patents of Ukraine on a useful model.
Keywords: функціональний жировий продукт; special fatty product; рослинна олія; технологія купажування; харчова цінність; oil; drowned adipose; technology of blending fat; fatty acid composition; food value; кафедра технології жирів, хімічних технологій харчових добавок та косметичних засобів